The life of René Malaise: from the wild east to a sunken island - Vårdal, Hege; Taeger, Andreas (Zootaxa, 2011)
A review is presented of the life of the Swedish entomologist René Malaise (1892–1978), the inventor of the “Malaise trap” and one of the most important 20th Century specialists on sawflies (Hymenoptera: Symphyta).